Condições semióticas da totalidade: a dupla leitura de Os dragões não conhecem o paraíso - Sousa, Vinícius Façanha Câmara de (2023)
Mereological relations, that is, the relations that are established between the parts of a totality or between the parts and the totality, are relevant in the process of meaning, for the readings of an isolated text and inserted into a set of texts can produce different meanings. The discursive semiotics is not alien to this theme, present since its foundation, but it approached it in a dispersed manner during its course in different theoretical forays. Thus, with this research we intend to put different perspectives face to face and verify their coherence and applicability in relation to objects of analysis and the epistemological principles that guide the discipline. In this sense, we chose the book Os dragões não conhecem o paraíso (Abreu, 2018 [1988]), which presents a double possibility of reading (collection of short stories and “mobile-novel”), as a corpus of analysis in order to observe which textual strategies allow the construction of distinct totalities and how the mereological dimension contributes to the production of different meanings in each reading option. To do so, we will take the categories stabilized by discursive semiotics in Greimas and Courtés (2021 [1979]) and the tensive approach developed by Fontanille and Zilberberg (2001 [1998]) and Zilberberg (2011 [2006]) and the sociosemiotics of Landowski (2014) as an analytical basis. Our proposal to surround the mereological dimension is based on the degrees of intimacy formulated by Hjelmslev (1978), on the types of mereological composition defined by Bordron (1991) and Fontanille (1999), as well as on the significant potential of sequencing, commented for example by Mafra (2019). Furthermore, to try to answer the question of how the same linguistic materiality can give rise to two different texts, we resort to the proposals of Fontanille (1999, 2008), respectively, around genres and the reading practice. With the same objective, we also discuss the relationship between enunciative praxis and connotation that enable the constitution of this object. At the end of our analyses, it was possible to verify how different textual strategies present in the work allow it to be identified in one genre or another, at the same time that the reading protocol selected by the enunciatee will guide his perception towards the realization of different meanings. among those updated in the book.